Pengaruh Metode Gallery Walk Terhadap Hasil Belajar Seni Rupa Siswa Kelas IV Sekolah Dasar - Sri Mulyani, Dwi; Anggraini, Dwi; Susanti, Atika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Gallery Walk method on Fine Arts knowledge learning outcomes among fourth-grade students at Elementary Schools in Gugus XIV, Bengkulu City. This research is quantitative in nature. The researchmethod used is Quasi-Experimental Design with The Matching Only PretestPosttest Control Group Design as the research design. The population of this study was fourth-grade students of State Elementary Schools in Gugus XIV, Bengkulu City, that have been accredited A. The research sample comprised students from Class IV A and Class IV B at Public Elementary School 42, Bengkulu City, selected using the Cluster Random Sampling technique. The research instrument used was a knowledge-based learning achievement test in the form of multiple-choice questions administered as a pretest and posttest. Data analysis in this studyemployed quantitative analysis using descriptive statistics, prerequisite tests, and hypothesis testing through the t-test. Based on the research findings, a Sig. (2- tailed) value of 0,002 < 0,05 was obtained at a significance level of 5%. The mean score of the experimental class (63,63) was higher than that of the control class (47,90), indicating a significant difference in learning outcomes between the experimental class and the control class. Therefore, it can be concluded that the Gallery Walk method has a significant effect on Fine Arts knowledge learning outcomes among fourth-grade students at Elementary Schools in Gugus XIV, Bengkulu City.